Emergence Delirium: Can Corticosteroids Contribute to It? - Esmel-Vilomara, Roger; Cruz, Alejandro; Inoriza, Cristina; Andreu, Eva; Munar, Francisca (Journal of Pediatric Intensive Care, 2020)
We report a case of emergence delirium after a propofol-based sedation for a renal biopsy in a teenager patient who had received high-dose and long-term corticosteroid treatment. Corticosteroid treatment is proposed as a possible risk factor for emergence delirium, although controlled studies are needed to assess this relationship. Although treatment for emergence delirium has not been well established, as described with steroid-induced psychiatric symptoms, antipsychotics could be a good therapeutic option.
Keywords: emergence delirium; corticosteroid; haloperidol